Effectiveness of EndoActivator, PATS Vario system, and XP-endo Finisher files on smear layer removal under scanning electron microscope: A comparative study - Rishabh Patel; Gaurav Shinde; Prashant Bondarde; Aruna Vishwakarma; Madhuri Bhandare; Vaibhavi Pharne (Wolters Kluwer Medknow Publications, 2024)
Context: The smear layer may harbor many bacteria; hence, alternative methods are used to disrupt and remove biofilm. AIM: The aim of the study was to compare the effectiveness of EndoActivator, PATS Vario System, and XP-endo Finisher files on smear layer removal using a scanning electron microscope. Subjects and Methods: Sixty single-rooted extracted premolars with Vertucci Type 1 configuration were decoronated and divided into four groups. The groups were instrumented with the rotary ProTaper file system. All specimens were flushed with 1 ml of 3% sodium hypochlorite. Group 1 was irrigated with a conventional needle and syringe. In Group 2, the irrigant was activated with an EndoActivator. In Group 3, the irrigant was activated with PATS Vario system, and in Group 4, XP-endo Finisher files were used after biomechanical preparation to remove debris and smear layer. All specimens were finally rinsed with 3 ml of 3% sodium hypochlorite. The teeth underwent longitudinal splitting and grooving in the coronal, middle, and apical thirds, and then, the samples were taken for scanning electron microscopy to evaluate the amount of smear layer removal in each third. Results: The middle and coronal thirds Showed that almost similar efficacy to remove smear layer in both Group II and Group III. At the apical third, Group III showed comparatively better results than Group I, II, and IV, respectively. Conclusion: Equal amount of smear layer was seen with EndoActivator and PATS Vario system when used as sonic irrigation devices.